1 - Globalizing Higher Education for Neo-liberal Development in Postcolonial Mozambique - Adelino Leonardo Chissale (Journal of Higher Education in Africa, 2012)
This article examines the ways in which neo-liberal discourses of globalization and development have been used to imagine and enact higher education in Mozambique. It argues that higher education developments in Mozambique in the past fifteen years are not only reflective of free market economy logic, but also ignore the social and historical contextualities, a course which deepens social inequalities. Using a postcolonial perspective to de-naturalize neo-liberal regimes of knowledge production, the article analyses how the course of higher education in Mozambique is indicative of broader social (trans)formations. It shows how the policy framework evokes and puts to work a set of technologies such as self-empowerment, self-regulation and a culture of managerialism to enforce the belief that individuals can make choices to fulfil their hopes of improving lives through higher education. It also argues that this belief does not take into account how such technologies of hope are configuring power relations which may lead, in the long run, to social inequalities because very few households can afford access to higher education.